La enseñanza del Derecho Aeronáutico - Capaldo, Griselda (2009)
This article is divided into four parts. It begins with a brief historical and contextual overview of the scientific developments that led to the birth of Aeronautical Engineering and, consequently, Aeronautical Law. It then reviews the curricular placement of Aeronautical Law in the curricula of Argentine universities and some other South American and European institutions. The third part addresses the teaching strategies employed for this subject, while the fourth and final part presents the results of an ongoing survey, conducted at the end of each academic year, among students who took the course between 2000 and 2009.